Relationship between Dental Caries Risk Factors and Quality of Life in Elementary School Children - Wiworo Haryani; Irma HY Siregar; Etty Yuniarti (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2021)
The prevalence of dental caries among children in Indonesia is still high. Riskesdas data in 2018 shows that children aged 8-12 years are vulnerable to dental caries problems. Dental caries have an impact on children's quality of life. The purpose of this study was to determine the relationship between risk factors for dental caries and children's quality of life and the magnitude of the influence of each risk factor. This type of research is analytic observational with a cross-sectional design. The population is elementary school children in the area of Banyuraden, Gamping, Sleman, Yogyakarta. The time of the study was from March 2021 to August 2021. The sampling technique was carried out by purposive sampling; the number of samples was 200 children. The influence variable is the risk factor for dental caries, and the affected variable is the child's quality of life. The research instrument is a questionnaire consisting of 30 statement items. Assessment of dental caries risk factors includes knowledge of caries, tooth brushing behavior, and cariogenic food eating habits. In contrast, assessing children's quality of life is seen from oral cavity complaints, functional complaints, psychological complaints, and limitations of social interaction. Data were analyzed by univariate, bivariate, and chi-square tests. The results showed more children with low quality of life (67.0%) than children with high quality of life (33.0%). The chi-square correlation test results showed a significant relationship between knowledge about dental caries and children's quality of life (p=0.002; OR=2.77), between tooth brushing behavior and children's quality of life (p=0.012; OR=2.14). as well as between the habit of eating cariogenic foods with the quality of life of children (p=0.020; OR=2.03). This study concludes a significant relationship between knowledge, behavior, and eating habits with children's quality of life.